Povezave relativne starosti z antropometričnimi spremenljivkami in živčno-mišično zmogljivostjo mladih slovenskih nogometašev - Smajla, Darjan (Šport (Ljubljana), 2023)
The aim of the study was to identify the differences in anthropometric measures and neuromuscular capacity in young Slovenian football players born in the first half (P1) and the second half (P2) of the calendar year in two different categories (U16 and U17). In total, 58 football players from the football club Tabor Sežana and the football department Gymnasium Šiška volunteered to participate in this study. Body height, mass, maximal strength (knee, ankle, nordic hamstring exercise) and push-off strength (squat jump, countermovement jump) was measured. Our results showed that U16 players born in P1 are statistically higher and heavier than players born in P2. Moreover, U16 players born in P1 have greater maximal strength in the nordic hamstring exercise and ankle dorsiflexion, while U17 players born in P1 have greater strength in ankle extension and nordic hamstring exercise compared to players born in P2. Based on our results, we can confirm that there are differences in anthropometric characteristics and performance in the sample of young Slovenian football players. In accordance with other studies, greater differences can be seen in younger players who are still in the maturation process.
Keywords: antropometrija; jakost; nogomet; nogometaši; odrivna moč; starost; šport